Hintikka, Jaakko, “Why Parallel Processing?”, in: Casati/Smith/White (Hg.) 1994 [Zbl 0849.00032], 265–272 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Echeverria, Javier, “Observations, Problems and Conjectures in Number Theory — The History of the Prime Number Theorem”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [ Zbl 0839.00019], 230–252 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Grattan-Guinness, Ivor, “Structure-similarity as a Cornerstone of the Philosophy of Mathematics”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [ Zbl 0839.00019], 91–111 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Otte, Michael, “Constructivism and Objects in Mathematical Theory”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl. 0839.00019], 296–313 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Torretti, Roberto, “Mathematical Structures and Physical Necessity”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 132–140 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Breger, Herbert, “Tacit Knowledge in Mathematical Theory”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 79–90 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

MacLane, Saunders, “The Protean Character of Mathematics”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [ Zbl 0839.00019], 1–13 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Howson, Colin, “Mathematics in Philosophy”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 192–201 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Heinzmann, Gerhard, Zwischen Objektkonstruktion und Strukturanalyse. Zur Philosophie der Mathematik bei Jules Poincaré, Vandenhoeck & Ruprecht: Göttingen 1995 (= Studien zur Wissenschafts-, Sozial- und Bildungsgeschichte der Mathematik; 10) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Resnik, Michael D., “Applying Mathematics and the Indispensability Argument”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 115–131 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Mosterín, Jesús, “Theories and the Flow of Information”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 367–378 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Dathe, Uwe, „Gottlob Frege und Rudolf Eucken - Gesprächspartner in der Herausbildungsphase der modernen Logik“, History and Philosophy of Logic 16 (1995), 245–255 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Knobloch, Eberhard/Pieper, Herbert/Pulte, Helmut, „...das Wesen der reinen Mathematik verherrlichen“, Mathematische Semesterberichte 42 (1995), 99–132 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Quesada, Daniel, “State of Affairs and the Evolution of Carnap’s Semantics”, Logique & Analyse Nouv. Sér. 36 (1993), 149–157 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Woleński, Jan, “Mathematical Logic in Poland 1900–1939: People, Circles, Institutions, Ideas”, Modern Logic 5 (1995), 363–405 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Murawski, Roman, “Contributions of Polish Logicians to Decidability Theory”, Modern Logic 6 (1996), 37–66 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Jean Piaget zur Einführung - Scharlau, Ingrid

Wissenserwerb und Raumreferenz. Ein sprachpsychologischer Zugang zur mentalen Repräsentation - Buhl, Heike M.

Erwerbssituation, mentale Repräsentation und sprachliche Lokalisationen - Blickpunktinformation als Bestandteil der Raumrepräsentation - Buhl, Heike M. (Sprache und Kognition)
Explored the question of point of view as a part of the mental representation of space. Human Ss: 80 normal German adults (university students) (Exp 1). 48 normal German adults (university students) (Exp 2). Ss participated in 2 separate experiments in which spatial expressions were taken to indicate the point of view in mental representation and in which one object was localized within a route direction context. Results were discussed as to whether working memory load offers an explanation for the availability of viewpoint oriented information that allows for changes in mentally represented point of views.

"Verschleiertes Geschlecht". Zum subversiven Potential des Fetisch bei Judith Butler und Marjorie Garber - Öhlschläger, Claudia; Deuber-Mankowsky, Astrid; Konnertz, Ursula (Die Philosophin. Forum für feministische Theorie und Philosophie. Heft 13/April 1996: Fetisch. Frau)

Forumsbeitrag: Bericht über das Münchner Graduiertenkolleg Geschlechterdifferenz und Literatur - Öhlschläger, Claudia (Der Deutschunterricht 1/1996: Differenzen - diesseits und jenseits von Geschlechterfixierungen (Hg.) Eva Kublitz-Kramer und Eva Neuland)

Sagen können, wie es hier ist, werd ich ja nie. Bildlektüren des Unbeschreiblichen in Rainer Maria Rilkes Briefen aus Spanien (1912/13) - Öhlschläger, Claudia (Hofmannsthal- Jahrbuch 4)

Unsägliche Lust des Schauens. Die Konstruktion der Geschlechter im voyeuristischen Text - Öhlschläger, Claudia

Lamellar lyomesophases under shear as studied by deuterium nuclear magnetic resonance - Lukaschek, M.; Müller, S.; Hasennindl, A.; Schmidt, Claudia; Grabowski, D. A. (Colloid & Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Solid State NMR Investigation of C1-Deuterated Poly(di-n-hexylsilylene) - Müller, Christian; Schmidt, Claudia; Frey, Holger (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Texte – Konstitution, Verarbeitung, Typik

A Review of A History of Women Philosophers. Hrsg. von Mary Ellen Waithe. New York u.a.: Springer 1987-1995: Review - Hagengruber, Ruth Edith (Sudhoffs Archiv)

Sicherheitserziehung - ein Thema für den Arbeitslehreunterricht. - Bigga, Regine (ARBEIT UND TECHNIK in der Schule)

Interaktiver Produktdatenaustausch mit EDIFACT - Aisch, H.; Joosten, M.; Müller, Wolfgang; Buijs, F.

Integrating a Constraint Solver into a Real-Time Animation Environment - Griebel, P.; Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C.; Uhr, H. (Proceedings of the 1996 IEEE Symposium on Visual Languages)
Investigates the integration of an interactive constraint solver into an existing 2D real-time animation environment in order to achieve a better observability, traceability and stability of the individual graphical objects. We present two approaches for assigning constraints to the objects. The first approach assigns constraints to the objects when they are created, keeping them stable during their entire life-time. The second approach dynamically changes constraints before the computation of each frame. The investigation is based on our practical experience with the complete visual programming language Pictorial Janus and the parallel constraint solver Parcon.
Keywords: Animation; Layout; Computer languages; Visualization; Observability; Stability; Runtime; Costs; Graphics; Hardware

Lebendig tot und oft begraben. Zur Absenz der Mutter bei Ingeborg Bachmann, Marlen Haushofer und Unica Zürn - Morrien, Rita (Mutter und Mütterlichkeit. Wandel und Wirksamkeit einer Phantasie in der deutschen Literatur)

Chirped fiber Bragg gratings for optical dispersion compensation: How to improve their fabrication accuracy - Sandel, D; Noé, Reinhold (22ND EUROPEAN CONFERENCE ON OPTICAL COMMUNICATIONS, PROCEEDINGS, VOLS 1-6: CO-LOCATED WITH: 2ND EUROPEAN EXHIBITION ON OPTICAL COMMUNICATION - EEOC ‘96)

Specification and Analysis of Concurrent Systems in a Complete Visual Environment - Dücker, Marita; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the 10th European Simulation Multiconference (ESM'96))

Visual Modeling and 3D-Representation with a Complete Visual Programming Language --- A Case Study in Manufacturing - Geiger, Christian; Hunstock, R.; Lehrenfeld, Georg; Müller, Wolfgang; Quintanilla, J.; Tahedl, C.; Weber, A. (Proceedings of the 1996 IEEE Symposium on Visual Languages)
The main goal of the article is to evaluate the suitability of visual programming languages, i.e., Pictorial Janus (K. Kahn and V. Saraswat, 1990), for the modeling of complex systems and their control strategies. These systems can be seen as networks of communicating objects. Objects select strategies for suitable actions based on incoming messages. Our field of investigation is in computer integrated manufacturing considering the example of a car manufacturing cell. This color sorting assembly buffer (CSAB) schedules jobs in queues. The jobs represent car bodies scheduled in feeder lines for the enameling. Feeder lines collect raw bodies to blocks. Blocks are bodies which are to be enameled by the same color. This organization decreases the cost of expensive change-over-times when changing colors at the enamelling. Blocks of bodies are dislocated from the queue and enameled successively. Contradictory system goals, such as minimizing color changes and preserving the sequence of incoming jobs, have to be regarded by appropriate control strategies. Due to the complexity of this (NP complete) problem and to real time requirements for online control there are no optimal strategies on hand. Consequently, suitable heuristics have to be developed. Often they are designed applying a trial-and-error method. A modeling framework has to support the rapid prototyping of these systems as well as an expressive end user oriented representation. Both are essential requirements since end users need other visualization techniques than experienced designers due to their different knowledge and interests.
Keywords: Computer integrated manufacturing; Job shop scheduling; Processor scheduling; Computer languages; Control system synthesis; Computer aided manufacturing; Sorting; Assembly; Costs; Control systems

Weibliches Textbegehren bei Ingeborg Bachmann, Marlen Haushofer und Unica Zürn - Morrien, Rita

Electric field-induced transition from the twist grain boundary TGBAphase to the tilted smectic SmC* phase - Kitzerow, Heinz-Siegfried; Slaney, Andrew J.; Goodby, John W. (Ferroelectrics)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Platinum Orthometalated Liquid Crystals Compared with Their Palladium Analogues. First Optical Storage Effect in an Organometallic Liquid Crystal - Buey, Julio; Díez, Laura; Espinet, Pablo; Kitzerow, Heinz-Siegfried; Miguel, Jesús A. (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

A Technique to Align Liquid Crystals Based on Bulk-Induced Photo-Polymerization - Jain, Sukhmal C.; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals Science and Technology. Section A. Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics

Gray‐scale in polymer‐stabilized antiferroelectric liquid crystal displays - Strauss, J.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Storage of laser-induced holographic gratings in discotic liquid crystals - Contzen, J.; Heppke, G.; Kitzerow, Heinz-Siegfried; Krüerke, D.; Schmid, H. (Applied Physics B Laser and Optics)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Effect of chirality on liquid crystals in capillary tubes with parallel and perpendicular anchoring - Kitzerow, Heinz-Siegfried; Liu, B.; Xu, F.; Crooker, P. P. (Physical Review E)

Polymer Dispersed and Polymer Stabilized Chiral Liquid Crystals - Kitzerow, Heinz-Siegfried (Liquid Crystals In Complex Geometries)

Polymer-dispersed liquid crystals: holographic formation of switchable gratings - Kitzerow, Heinz-Siegfried; Strauss, J.; Jain, Sukhmal C. (SPIE Proceedings)

Gebet einer Jungfrau. Ein Szenenprojekt für die Sekundarstufe II - Grotjahn, Rebecca (Musik und Bildung)

Theory of Macromolecular Rings - Huber, Klaus; Burchard, Walther (Large Ring Molecules)

Analyses of Sub 1/4-Micron MOS-Transistors by Visible Light Emission - Muller, J.; Wirth, G.; Hilleringmann, Ulrich; Goser, K. (ESSDERC ’96: Proceedings of the 26th European Solid State Device Research Conference)

Characterization and Matching Analysis of 50 nm-NMOS-Transistors - Horstmann, J. T.; Hilleringmann, Ulrich; Goser, K. (ESSDERC ’96: Proceedings of the 26th European Solid State Device Research Conference)

ESSDERC’96, Bologna, Italy - Horstmann, JT; Hilleringmann, Ulrich; Goser, K (Conf. Dig)

Coherent Dynamics of Semiconductor Heterostructures - Meier, Torsten; Koch, S.W.; Stroucken, T.; Knorr, A.; Hader, J.; Rossi, F.; Thomas, P. (Microscopic Theory Of Semiconductors: Quantum Kinetics, Confinement and Lasers)

Dephasing of interacting heavy-hole and light-hole excitons in GaAs quantum wells - Meier, Torsten; Bott, K.; Mayer, E.J.; Smith, G.O.; Heuckeroth, V.; Hübner, M.; Kuhl, J.; Schulze, A.; Lindberg, M.; Koch, S.W.; Thomas, P.; Hey, R.; et al. (Journal of the Optical Society of America B)
We describe a novel three-pulse degenerate four-wave mixing configuration that permits the direct observation of the coherence between the σ+ and the σ− exciton states in a GaAs quantum well excited in a two-photon process. It is found that the phase coherence between the two single heavy-hole exciton states decays with a time constant that is considerably longer than the dephasing time of the coherence between these states and the ground state (interband coherence). All the experimental data are well described by numerical solutions of the optical Bloch equations for a phenomenological multilevel model.

Körper :-) Wahrnehmung. Eine Seminarübung mit Dietriu Zilleßen - Schroeter-Wittke, Harald; Fermor, Gotthard; Zilleßen, Dietrich (Prozesse postmoderner Wahrnehmung. Kunst - Religion - Pädagogik)

Homiletische Überlegungen zu I Kön 18 - Schroeter-Wittke, Harald; Schroeter, Britta (Elia. Ein Prophet in dürrer Zeit - Materialien zur Gottesdienstgestaltung. Thema: Gottesdienst)

Der Dienst der öffentlichen Verkündigung in einer missionarischen Situation - Schroeter-Wittke, Harald (Der Dienst der öffentlichen Verkündigung in einer missionarischen Situation)

Kirchentag als Gesamtkunstwerk. Ein Bericht über seine kulturellen Dimensionen - Schroeter-Wittke, Harald (Kirche und Kultur der Gegenwart)

"Schweigendes Buch" - Zu einer Kunstaktion des Siegburger Künstlers Robby Gebhardt - Schroeter-Wittke, Harald (Thema: Gottesdienst)

"Schweigendes Buch" - Zu einer Kunstaktion von Robby Gebhardt - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

On the Observability of dynamic localization in semiconductor superlattices using optical spectroscopy - Meier, Torsten; Rossi, F.; Je, K.-C; Hader, J.; Thomas, P.; Koch, S.W. (Hot Carriers in Semiconductors)
During the last decade, a variety of field-induced coherent phenomena in semiconductor superlattices has received considerable attention both from a theoretical and from an experimental point of view. For the case of a static applied electric field, the existence of Bloch oscillations has been predicted theoretically and confirmed by means of different experimental techniques of nonlinear optical spectroscopy.

Microscopic theory of the Bloch-oscillation dynamics in semiconductor superlattices: Intra- versus interband Dephasing - Meier, Torsten; Rossi, F.; Gulia, M.; Selbmann, P.E.; Molinari, E.; Thomas, P.; Thomas, P.; Koch, S.W. (Proceedings of the 23rd ICPS)

Exciton ionization induced by an electric field in a strongly coupled GaAs/AlxGa1-xAs superlattice - Meier, Torsten; von Plessen, G.; Koch, M.; Feldmann, J.; Thomas, P.; Koch, S.W.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Physical Review-Section B-Condensed Matter)
We study exciton ionization induced by an axial electric field in a strongly coupled GaAs/Al0.3Ga0.7 As superlattice at low temperatures. The field-induced ionization times of the heavy-hole 1s exciton in the miniband field regime are determined from transient four-wave-mixing experiments and theoretical model calculations. They are found to decrease with increasing field, and lie in the picosecond and subpicosecond ranges for fields on the order of a few kV/cm. They are considerably longer than those calculated for a 1s exciton in bulk GaAs. We explain this difference as a result of the nonparabolicities in the superlattice miniband dispersion. In addition to studying the field-induced ionization of the 1s resonance, we also investigate the field dependence of excitonic wave packets composed of both bound and continuum states of the exciton. It is found that the continuum components of the wave packet are more sensitive to low electric fields than the 1s component. © 1996 The American Physical Society.

Disorder mediated biexcitonic beats in semiconductor quantum wells - Meier, Torsten; Albrecht, T.F.; Bott, K.; Schulze, A.; Koch, M.; Cundiff, S.T.; Feldmann, J.; Stolz, W.; Thomas, P.; Koch, S.W.; Göbel, E.O. (Physical Review B)
Beats in the transient four-wave-mixing signal from strongly inhomogeneously broadened semiconductor quantum wells are observed. Based on their phase and polarization properties, the beats are assigned to biexcitons in the mesoscopically disordered material. With increasing excitation intensity a halving of the beat period is observed and is accurately reproduced by calculations including fifth-order contributions.

Femtosecond Spectroscopic Signatures of Electronic Correlations in Conjugated Polyenes and Semiconductor Nanostructures - Meier, Torsten; Mukamel, S. (Physical review letters)
Electronic correlation effects which can be directly probed by ultrafast four-wave mixing are predicted using the electronic-oscillator representation of conjugated polyenes. Comparison with inorganic semiconductors is made possible since the semiconductor Bloch equations projected onto the lowest exciton are obtained as a limiting case. A sign difference in a nonlinear scattering potential clearly shows up in the Wigner spectrogram representing the time and frequency resolved signal.

Prozesse postmoderner Wahrnehmung. Kunst - Religion - Pädagogik. Ein Schrift-Fest für Dietrich Zilleßen zum 60. Geburtstag

Field-induced exciton ionization studied by four-wave mixing - Meier, Torsten; Koch, M.; von Plessen, G.; Feldmann, J.; Koch, S.W.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Hot Carriers in Semiconductors)
The dynamics of carriers induced by electric fields in semiconductor superlattices has received much interest in recent years. Phenomena like Bloch oscillations and negative differential velocity in these structures have been studied using a variety of experimental techniques [1–5]. One particular point of interest has been the transition of the miniband regime to the Bloch oscillation regime with increasing electric field [6,7]. Cw spectra of strongly-coupled superlattices have evidenced that this transition is concomitant with a rapid field-induced ionization of the zero-field miniband exciton [5,8]. While it has been pointed out from the theoretical side that the field-induced ionization process strongly influences the coherent dynamics in the transition region [9], no systematic experimental investigation of the ionization process has been carried out so far. One interesting question that such an investigation could help to answer is to what extent this ionization process differs from the well-documented case of field-induced exciton ionization in bulk semiconductors.

Equilibrium and nonequilibrium optical effetcs in semiconductor heterostructures - Meier, Torsten; Koch, S.W.; Hader, J.; Je, K.-C; Rossi, F.; Thomas, P. (Frontiers in Nanoscale Science of Micro/Submicro Devices)

Phonon-Induced Suppression of Bloch Oscillations in Semiconductor Superlattices: a Monte Carlo Investigation - Meier, Torsten; Rossi, F.; Thomas, P.; Koch, S.W.; Selbmann , P.E.; Molinari, E. (Hot Carriers in Semiconductors)
The progress in the generation of ultrashort laser pulses, together with the development of spectroscopies on this time-scale, has led to a series of experiments which give new insight into the microscopic carrier dynamics in semiconductors. In particular, the energy relaxation of photoexcited carriers has been widely investigated. At the same time, recent progress in the fabrication and characterization of semiconductor heterostructures and superlattices allows a detailed study of a new class of phenomena induced by an applied electric field, such as Bloch oscillations1,2. Both classes of phenomena typically occur on a pico- or femtosecond time-scale, where the coupling between coherent and incoherent phenomena is known to play a dominant role3. Therefore, an adequate theoretical model of the ultrafast dynamics on this time-scale must account for both coherent and incoherent effects on the same kinetic level.

Euler’s theorem and map color problems - Burban, Igor (U sviti Mathematyky)

Solutions of equations in integers - Burban, Igor (U sviti Mathematyky)

Evaluation der Fortbildung „Lesen in der Sekundarstufe I“. - Herzig, Bardo; Mütze, Ch.; Tulodziecki, G. (Mehr als ein Buch. Leseförderung in der Sekundarstufe I.)

Erprobungen und Evaluationen zur Verwendung und zur Förderung einer verantwortungsbewußten Nutzung neuer elektronischer Medien - Herzig, Bardo (Neue Medien in den Schulen. Projekte, Konzepte, Kompetenzen)

Evaluation der Fortbildung „Lesen in der Sekundarstufe I“ - Herzig, Bardo; Mütze, Ch.; Tulodziecki, G. (Mehr als ein Buch. Leseförderung in der Sekundarstufe I)

Neue Medien in den Schulen. Projekte – Konzepte – Kompetenzen. - Tulodziecki, G.; Hagemann, W.; Herzig, Bardo; Leufen, S.; Mütze, Ch.

Ethische Orientierung im Informatikunterricht - Herzig, Bardo (LOG IN 16(1996)3)

„Ja wend das blat vmb, szo findistu es“. Zum Gebrauch textstrukturierender und textkommentierender Äußerungen in frühneuhochdeutschen Flugschriften - Schuster, Britt-Marie (Bausteine zu einer Geschichte des weiblichen Sprachgebrauchs. Forschungsberichte – Methodenreflexion)
Keywords: Textsortengeschichte

Die Revolution, der Schrecken und das Neue. Konzepte von Legitimität und historischer Gewalt in deutschen Revolutionsdramen um 1800 - Eke, Norbert Otto (Literatur und Erfahrungswandel 1789-1830. Beiträge des 2. Internationalen Corvey-Symposions 8.-12. Juni 1993 in Paderborn)

So ist von uns zu Recht erkannt. Überlegungen zu den Rechtsgrundlagen von Zauberei- und Hexenprozessen im Spiegel der Carolina und verwandter Rechtsquellen im Alten Reich - Ströhmer, Michael

Unitary Highest Weight Representations via the Orbit Method I: The Scalar Case - Hilgert, Joachim; Neeb, K.-H.; Orsted, B. (Acta Appl.. Math.)

Conal Heisenberg Algebras and Associated Hilbert Spaces - Hilgert, Joachim; Neeb, K.-H.; Orsted, B. (J. reine angew. Math.)

Orthogonal Lie Algrebras with Cone Potential - Hilgert, Joachim; Neeb, K.-H. (Commun. in Alg.)

Spherical Functions on Olshanskii Spaces - Hilgert, Joachim; Neeb, K.-H. (J. Funct. Anal.)

Knapp, A.W. Lie Groups Beyond an Introduction (Birkhäuser, Boston, 1996) - Hilgert, Joachim (Zentralblatt für Math.)

Realitätsorientierte Wissenschaft oder praxisfernes Traditionswissen? Inhalte und Probleme mittelalterlicher Wissenschaftsvorstellungen am Beispiel von 'De temporum ratione' des Beda Venerabilis - Englisch, Brigitte (Dilettanten und Wissenschaft: Zur Geschichte und Aktualität eines wechselvollen Verhältnisses)

Die älteste urkundliche Erwähnung Meinerzhagens (1067) vor dem Hintergrund der Grundherrschaften und Besitzverhältnisse Südwestfalens im Hohen Mittelalter - Englisch, Brigitte (Der Märker)

Projection and methods of mapping in Erhard Etzlaub's cartographical works - Englisch, Brigitte (Imago Mundi. The international journal for the history of cartography)